Contemporary International Treaties Seen From the Principles of Maqasid Ash-Shariah - Nugraha, Amal Teguh (Universitas Muhammadiyah Surakarta, 2022)
Along with the times, the pattern of human interaction continues to evolve. Finally the human communication penetrates the boundaries of nation and state. The pattern which forms the inevitable urgency produces an International Treaties. However, an international treaty in Islam could be accepted if it is in line with Islamic Law, then it is processed into Maqasid Ash-Shariah. This research includes two important issues, ''Islamic relation and global society